"An Exercise in Telemachry": David Foster Wallace's Infinite Jest and Intergenerational Conversation. Issue 4 (7th August 2016) - Bartlett, Christopher
ABSTRACT: This article examines David Foster Wallace's Infinite Jest alongside its eponymous film, arguing that they share a common purpose, but that the former succeeds where the latter fails. Coupled with a biographical and phenomenological analysis, the aim of this examination is to better understand Infinite Jest 's place in the cultural and literary movement away from postmodernism. Through the novel, Wallace seeks a cure for the postmodern malaise that is irony, which creates a distancing effect between author and reader. I argue that he collapses this distance by creating a conversation-like novel that uses sentimentality and endnotes to converse with a generation bombarded with easily consumable irony from television, advertisements, and even art. The results of this conversation are the curtailing of passive consumption of entertainment and the beginning of a new sincerity in literature, which allows for grand narratives without the unending cynicism of postmodernism.